IMPACT OF POINT OF PURCHASE ADVERTISING IN SALES - Tripathi, Dr Prashant (Innovative Research Thoughts, 2018)
The primary aim of advertisement is to boost the sale of a product by continuously introducing the product to the customer. However, it is possible that at the time of retail purchase, customers will purchase another product. This emphasizes the importance of point of purchase advertisement. "Purchase advertising or POP" are marketing materials that merchants employ in their shops to promote goods, attract attention and encourage customers to purchase. It also refers to the strategic positioning of goods in the shop. This paper aims to review past works of literature for creating a base for a better understanding of Point of Purchase advertising and associated methods.